Asuhan Keperawatan Pada Pasien Dengan Penyakit Hipertensi Di Ruang Interne RSUD Prof H. Muhammad Yamin SH Pariaman - Afifah Nursyah; Debby Silvia Dewi; Hilma Yessi; Linda Marni (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hypertension is a condition caused by problems in the circulatory system, resulting in blood pressure rising above normal levels. According to the World Health Organization (2025), hypertension is the leading cause of premature death worldwide. Based on the Indonesian Health Survey (2023), there were 63,309,629 cases of hypertension, resulting in 427,218 deaths. The Pariaman City Health Department (2024) reported that the prevalence of hypertension in West Sumatra is approximately 25.16%, or about 176,169 people. The highest prevalence rate was found in the city of Bukittinggi at 41.8%, and the lowest in the city of Pariaman at 20.2%. Medical records from Prof. H. Muhammad Yamin SH Pariaman General Hospital indicate that there were 5 cases in 2025. The objective of this case study is to gain an understanding of the implementation and ability to apply comprehensive nursing care for patients with hypertension. The method used in this scientific paper is the case study method, conducted in the internal medicine ward of Prof. H. Muhammad Yamin SH General Hospital in Pariaman from January 31, 2026, to February 4, 2026. The nursing issues identified in the patient were decreased cardiac output, acute pain, risk of ineffective peripheral perfusion, risk of bleeding, and knowledge deficit.  The intervention was implemented over 5 days, resulting in the following improvements for the patient: reduced pain complaints, improved pulse rate, reduced fatigue, reduced pallor, improved acral circulation, improved skin turgor, improved skin moisture, increased adherence to recommendations, and increased behavior consistent with knowledge. It is recommended that the patient take medication regularly and that the patient and family adopt a healthy lifestyle, as well as undergo routine check-ups at a healthcare facility to stabilize blood pressure.